The Monotonicity Results for the Ratio of Certain Mixed Means and Their Applications - Zhen-Hang Yang (International Journal of Mathematics and Mathematical Sciences)
We continue to adopt notations and methods used in the papers illustrated by Yang (2009, 2010) to investigate the monotonicity properties of the ratio of mixed two-parameter homogeneous means. As consequences of our results, the monotonicity properties of four ratios of mixed Stolarsky means are presented, which generalize certain known results, and some known and new inequalities of ratios of means are established.